ANALISIS PENERAPAN MODEL PROJECT BASED LEARNING PADA PELAJARAN PPKN KELAS I SD NEGERI GAJAHMUNGKUR 04 SEMARANG - Diah Ayu Kusuma Dewi; Aries Tika Damayani; Ganis Suprihatini (LPPM Universitas Cipta Mandiri, 2024)
The aim of this research is to describe the application of the Project Based Learning (PjBL) model in class 1 PPKN learning at SD Negeri Gajahmungkur 04 Semarang. This research uses a qualitative descriptive method, with observation and documentation techniques to collect data. The data source for this research was class I students at SD Negeri Gajahmungkur 04. The data obtained was analyzed in three stages, firstly data collection, secondly data presentation, thirdly drawing conclusions. The results of this research indicate that the application of the Project Based Learning (PjBL) model in PPKN learning at SD Negeri Gajahmungkur 04 Semarang is effective in improving learning outcomes and developing student character. The implementation of the PjBL learning model is carried out in two stages, namely the preparation stage and the implementation stage. There are five stages of learning implementation, namely; (1) basic questions, (2) designing a product plan, (3) preparing a manufacturing schedule, (4) developing project results, (5) testing results. From the research results, it can be concluded that the application of the Project Based Learning (PjBL) model in class I PPKN learning at SD Negeri Gajahmungkur 04 Semarang is the appropriate learning model to be applied in PPKN learning in class I at SDN Gajahmungkur 04 Semarang. The results of research and discussions in implementing the PjBL model can provide positive results, making students active, creative and think critically.